2016
DOI: 10.1016/j.ijcha.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width (RDW) correlates with markers of diastolic dysfunction in patients with impaired left ventricular systolic function

Abstract: ObjectiveRed-cell distribution width (RDW) has been identified as a novel prognostic marker in a heterogeneous group of heart failure patients. In this group, diastolic dysfunction is associated with worse outcome. As the evidence is limited, the aim of the present study was to assess the relationship of RDW to diastolic markers in patients with left ventricular dysfunction (LVD) diagnosed during cardiac catheterization.MethodsClinical and angiographic data were collected retrospectively on a total of 291 stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…RDW has been shown to be a predictor of outcomes in patients with idiopathic pulmonary arterial hypertension [23]. Alattar et al [24] reported a positive correlation between RDW and SPAP in patients with heart failure with diastolic dysfunction. Hypoxia may trigger pulmonary arterial hypertension through vasoconstriction and structural vascular remodeling, such as smooth muscle hypertrophy and hyperplasia, in addition to collagen and elastin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…RDW has been shown to be a predictor of outcomes in patients with idiopathic pulmonary arterial hypertension [23]. Alattar et al [24] reported a positive correlation between RDW and SPAP in patients with heart failure with diastolic dysfunction. Hypoxia may trigger pulmonary arterial hypertension through vasoconstriction and structural vascular remodeling, such as smooth muscle hypertrophy and hyperplasia, in addition to collagen and elastin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a gradual accumulation of evidence suggesting that peripheral vascular endothelial dysfunction and abnormal ocular blood flow may play important roles in the PACG pathophysiology [35][36][37]. For instance, Alattar et al [38] showed that the RDW correlates with the diastolic vascular and vascular endothelial dysfunction markers [13]. Interestingly, several studies have reported that the vessel density in the optic nerve head region was decreased in PACG patients.…”
Section: Discussionmentioning
confidence: 99%